Systematic Literature Review on the Design and Prototype Testing of a Compact, Low-Cost, and Tropical Climate-Resilient Household Black Soldier Fly Larvae Cultivation System for Organic Waste Reduction at Source - Janatika Putra Perdana; Muhammad Syukri Nur; Milla Viendyasari; Tri Bagus Prabowo; Akhmad Muji Hartono (AIBPM Publisher, 2025)
The increasing volume of household organic waste in urban areas is a major challenge for sustainable environmental management, particularly in tropical regions with high temperatures and humidity. Black soldier fly larvae (BSFL) bioconversion offers an effective and sustainable solution by reducing organic waste while producing high-protein biomass. However, household adoption remains limited due to the lack of compact, affordable, and climate-appropriate cultivation systems. This study aims to identify and synthesize key design principles for a household-scale BSFL cultivation prototype optimized for humid and high-temperature tropical environments. A Systematic Literature Review was conducted to examine studies on bioconversion efficiency, environmental parameters, and system design characteristics. The findings highlight three main priorities: (1) the use of locally available low-cost materials to improve affordability and scalability; (2) an effective passive aeration system to control humidity and prevent mold growth; and (3) adequate thermal insulation to maintain stable internal temperatures. Based on the synthesized evidence, the proposed prototype is expected to achieve at least 50% organic waste reduction within 7–10 days, with a daily processing capacity of 1–3 kg. These findings provide practical guidance for accessible and sustainable BSFL-based waste management solutions in tropical urban settings.